Peranan Produk Pembiayaan Syariah Terhadap Perkembangan Usaha Di BMT Amanah Ummah Kartasura - Hanief, Abdul; , Lukman Hakim, SE, M. Si (2017)
This study aims to determine: (1) the role of sharia financing products to the business development of society, (2) to find out the obstacles that is being faced and how to overcome it on BMT Amanah Ummah Kartasura. This research uses a qualitative model with data collection techniques, using interview method, observation and documentation. The analysis technique of the qualitative data is by triangulation of source, method, time and theory. Data mostly obtained from interviews with the BMT, members, and some documentation from BMT Amanah Ummah. The results of the research are: 1) BMT positively contributes to the welfare of the community in various sectors: a) Trade Sector, financing is used for additional business capital and purchase members trade needs. b) Service Sector, used to buy workshop equipment on motorcycle and car body workshop services on Expeditionary Services. c) Household sector, used to renovate the house, finance education, childbirth, motorcycle bike and meet daily needs. 2) Obstacles faced by BMT Amanah Ummah: a) Obstacles in the field of human resources, the difficulty of adding human resources due to some prospective employees couldn't meet the criteria required by the BMT. b) Constraints in the field of Marketing, the existence of competitive competition among financial institutions in an area. c) Constraints in the field of Operations, the existence of non-current financing made by some members of BMT.